Scholastic Rabbinism : A Literary Study of the Fathers According to Rabbi Nathan - Saldarini, Anthony J.; Satlow, Michael L.; Andrew W. Mellon Foundation; National Endowment for the Humanities; Project Muse. (Chico : Scholars Press, 2020)
"Scholastic Rabbinism is a study of two early rabbinic documents, Pirke Avot and the Avot d'Rabbi Natan. Saldarini's study examines the literary connections between these related documents while at the same time drawing larger conclusions about their provenance and what they contribute to our understanding of early rabbinic scholasticism"--Provided by publisher
Introduction -- The Chapters of the Fathers -- The Literary Structure of The Fathers According to Rabbi Nathan -- The Thematic Development of The Chain of Tradition -- The Nature of The Chain of Tradition -- The School of Rabban Johanan Ben Zakkai and his Disciples: A New Way of Life -- The Sayings of The Early Sages -- The Enumeration Sayings -- Literary Conclusions -- Historical Conclusions.
"Licensed under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 International License."--T.p. verso
"Open access edition funded by the National Endowment for the Humanities/Andrew W. Mellon Foundation Humanities Open Book Program."--T.p. verso
"This edition incorporates typographical and some factual corrections of the original text."--Publishers' preface
Edition statement from online full metadata page.
Description based on print version record.
Keywords: Talmud; Talmud. -- Criticism, interpretation, etc; Jewish ethics; Morale juive; Jewish ethics; Livres numeriques; Criticism, interpretation, etc; e-books.; Electronic books